Musical Totem: A Collaborative Composition Methodology During the Covid-19 Pandemic - Carrillo, Víctor Manuel Rubio; Echeverría-Valencia, David; Vaca, Eliana Sofia; Prado, Sebastián López (CAML Review / Revue de l’ACBM, 2021)
As part of the Action Research Network of the Americas, the Musical Learning Community is a collaborative group, founded during the COVID-19 global pandemic, that has brought together musicians, artists, and educators to generate shared experiences. As members of this community, we explore new ways for collaborative music-making. Through creative, cultural, and conceptual influences, the idea of the Musical Totem emerged as a collaborative music composition methodology to transcend geographical distancing. We sought interpretative freedom by adopting methods of the surrealist technique Cadavre Exquis (Exquisite Corpse) while relying on the rich concept of totems to find thematic material and set compositional parameters. The process was carried out using arts-based and autoethnographic research approaches, which provided insights into our creative musical responses and remote collaborative working processes. This endeavor showed us that symbolism can provide compositional and performative challenges and that, as a methodology, the Musical Totem can create freedom and constraints depending on the musician, the conceptual influences, and the instrumentation. We also learned that engaging in a collaborative music-making process led to increased community bonding through shared creative expression.